Load calculation and strength analysis of floating garbage cleaning equipment - Xu Weiyao; Guo Jianting; Ji Chunyan (E3S Web of Conferences, 2021)
In order to alleviate the problem that there is increasingly floating garbage pollution on the sea, this paper proposes a new design of floating garbage cleaning equipment. This equipment is a slender structure, and whether its structural strength can meet the design requirements requires special attention. In order to ensure the rationality and safety of the design, load calculation and strength analysis are carried out based on the design wave method. The calculation results show that the longitudinal torque load of this equipment is the largest, which is 2.5 times of the second largest vertical bending moment. At the same time, there are three large stress areas in the floating structure, which are the connection between the pontoon and the connecting buntons, the connecting buntons intersecting with the Y axis and the pontoons on both sides. For the abovementioned high-stress areas, a structural strengthening plan is proposed. After the improvement, the stress in the high-stress areas of the structure is significantly reduced, with a maximum reduction of 52%. The strength of the improved structure meets the design requirements. The research results of this paper can provide relevant references for the development of floating garbage cleaning equipment in the future.